Liquid chromatography–electrospray ionization-tandem mass spectrometry for the determination of short-chain chlorinated paraffins in mixed plastic wastes. (April 2020) - Matsukami, Hidenori; Takemori, Hiroaki; Takasuga, Takumi; Kuramochi, Hidetoshi; Kajiwara, Natsuko
Abstract: Wastes containing short-chain chlorinated paraffins (SCCPs) at concentrations above the Basel Convention low persistent organic pollutant content (LPC) values must be destroyed or irreversibly transformed in an environmentally-sound manner. Here, we developed a novel liquid chromatography–electrospray ionization-tandem mass spectrometry (LC–ESI-MSMS) method for determining the concentrations of SCCPs in mixed plastic wastes. Major SCCP homologues were identified with good separation and peak width by using a low-hydrophobicity cyano-propyl column and a mobile phase consisting of water and methanol containing ammonium acetate. Precursor ion peaks corresponding to the formation of stable SCCP homologue–adducts were observed, followed by two intense product ion peaks corresponding to separation of the adduct into acetate and the homologue. The formulation of a novel calibration standard with known SCCP homologue percentage composition supported the development of our novel mass spectrometric technique. The results obtained with the LC–ESI-MSMS system were quantitatively and qualitatively comparable with those obtained with a high-resolution mass spectrometry (HRMS) coupled to gas chromatography (GC) system. Homologue concentrations determined by LC–ESI-MSMS were significantly correlated with those determined by GC–HRMS in samples of commercial chlorinated paraffin mixture and mixed plastic waste, respectively. As a complementary technique to the highly accurate, but less versatile GC–HRMS approaches, the SCCP analysis by LC–ESI-MSMS is a practical way to identify mixed plastic wastes containing SCCPs at concentrations higher than the Basel Convention's LPC value. Highlights: Novel mass spectrometric method to quantify SCCPs in plastic wastes was developed. Major SCCP homologues were identified with good separation and peak width. Present data were in good agreement with high-resolution mass spectrometry data. Plastic wastes containing SCCPs above Basel Convention limits can be identified.